Exogenous Activation of Invariant Natural Killer T Cells by α-Galactosylceramide Reduces Pneumococcal Outgrowth and Dissemination Postinfluenza - Adeline Barthelemy (American Society for Microbiology, 2016)
ABSTRACT Influenza A virus infection can predispose to potentially devastating secondary bacterial infections. Invariant natural killer T (iNKT) cells are unconventional, lipid-reactive T lymphocytes that exert potent immunostimulatory functions. Using a mouse model of postinfluenza invasive secondary pneumococcal infection, we sought to establish whether α-galactosylceramide (α-GalCer [a potent iNKT cell agonist that is currently in clinical development]) could limit bacterial superinfection. Our results highlighted the presence of a critical time window during which α-GalCer treatment can trigger iNKT cell activation and influence resistance to postinfluenza secondary pneumococcal infection. Intranasal treatment with α-GalCer during the acute phase (on day 7) of influenza virus H3N2 and H1N1 infection failed to activate (gamma interferon [IFN-γ] and interleukin-17A [IL-17A]) iNKT cells; this effect was associated with a strongly reduced number of conventional CD103+ dendritic cells in the respiratory tract. In contrast, α-GalCer treatment during the early phase (on day 4) or during the resolution phase (day 14) of influenza was associated with lower pneumococcal outgrowth and dissemination. Less intense viral-bacterial pneumonia and a lower morbidity rate were observed in superinfected mice treated with both α-GalCer (day 14) and the corticosteroid dexamethasone. Our results open the way to alternative (nonantiviral/nonantibiotic) iNKT-cell-based approaches for limiting postinfluenza secondary bacterial infections. IMPORTANCE Despite the application of vaccination programs and antiviral drugs, influenza A virus (IAV) infection is responsible for widespread morbidity and mortality (500,000 deaths/year). Influenza infections can also result in sporadic pandemics that can be devastating: the 1918 pandemic led to the death of 50 million people. Severe bacterial infections are commonly associated with influenza and are significant contributors to the excess morbidity and mortality of influenza. Today’s treatments of secondary bacterial (pneumococcal) infections are still not effective enough, and antibiotic resistance is a major issue. Hence, there is an urgent need for novel therapies. In the present study, we set out to evaluate the efficacy of α-galactosylceramide (α-GalCer)—a potent agonist of invariant NKT cells that is currently in clinical development—in a mouse model of postinfluenza, highly invasive pneumococcal pneumonia. Our data indicate that treatment with α-GalCer reduces susceptibility to superinfections and, when combined with the corticosteroid dexamethasone, reduces viral-bacterial pneumonia.